Lies, Stories, and Arguments: Can A Callipolis Exist Without the Noble Lie? - Tonguç Seferoğlu (Felsefe Arkivi)
During the second half of 20th century, Plato’s presentation of a theory of citizenship and government in the Republic has been accused of being totalitarian, racialist, and anti-egalitarian. In particular, the use of a noble lie as a propaganda tool to persuade citizens about a congenital politic and economic hierarchy has rightly been subjected to intense criticism. Although Plato would not be completely acquitted of all the charges against him, linguistic and logical analyses of the epistemic status and persuasive power of the noble lie can furnish one with a deeper comprehension of Plato’s philosophical purpose. I argue that (i) the noble lie is devised to motivate those who are educated to become philosopher-rulers to work for the good of the Callipolis and its citizens and that (ii) Plato did not expect the noble lie to be enough to persuade either the philosopher-rulers or the rest of the citizens about the goodness and advantages of the government of the Callipolis. This story can be used either for having those of the common people who read Plato’s Republic understand his ideal or for persuading the future citizens of Callipolis who are unpersuadable by rational arguments, should that ever come to be. In conclusion, this study seeks to establish Plato’s awareness of the facts that the noble lie does not ensure the foundation or stability of the Callipolis and that the noble lie is thus neither sufficient nor necessary for Plato’s political ideal.